IMPROVING STUDENTS’ VOCABULARY THROUGH SPOOF TEXT AT FIRST GRADE OF SMP NEGERI 1 SUNGGUMINASA - Rahmatia, Rahmatia (Teaching English as a Foreign Language Overseas Journal, 2022)
This study was to know the ability of students of SMP Negeri 1 Sungguminasa in mastering vocabulary by using spoof text. It was conducted at VII class of SMPN 34  Makassar academic year 2021/2022 as the subject of the study. This study is categorized as a collaborative classroom action research. The writer worked collaboratively with the English teacherin the class. The CAR was done based on Kurt Lewins’ design. The writer did two cycles in which each cycle consists of planning, acting, observing, and reflecting. The data were gathered through qualitative and quantitative data. The qualitative data was gained by analyzing observation result. Then, quantitative data were obtained from the students’ writing score of pretest and posttest. The finding of this study showed that there was an improvement on the students’ ability in vocabulary. It can be seen from the mean of pretest score was 60.31. Then, the mean of posttest cycle 1 score was 66.38 and the mean of posttest cycle 2 score was 75.31. In addition, there were 4 students (9.5%) who passed Minimum Mastery Criterion – Kriteria Ketuntasan Minimal (KKM) in the pre test. Meanwhile, in the cycle 1, there were 14 students ( 33.3%) who passed Minimum Mastery Criterion – Kriteria Ketuntasan Minimal (KKM) and it gained which was in the posttest cycle 2 there were 37 students (88%) who passed Minimum Mastery Criterion –  Kriteria Ketuntasan Minimal (KKM), so the criterion of success was achieved.  Related to the results of the gained data, it can be concluded that spoof text can improve students’ ability in vocabulary.